Calvin, Society, and Social Change - Paul Marshall (Reformed Center for Religion and Society, 2014)
ABSTRACT: For Calvin, the whole creation is equally under Gods sovereign will and the institutions of society are not arranged hierarchically but are differentiated according to vocation. Because of this differentiation, Gods calling is not mediated exclusively through one of them, so none can claim sovereignty over the others. They are to be arranged side by side in mutual support of one another, and Gods work is carried out by the free, voluntary obedience by Gods people. This led in turn to a stress on moving politics from being simply an elite occupation to one that is participatory– the response of human beings who freely submit themselves to God and thus seek to transform the social, economic and political to reflect Gods order. It also led to a covenantal view ofpolitics that helped create modern federalism.Â KEYWORDS:Â Althusius, associations, Calvin, federalism, freedom, popular participation, vocation, subsidiarity.